The Relationship Between Husband's Support and Postpartum Mother's Compliance in Making Return Visits to Bpm "F" Agam Regency (HEALTH CARE: JURNAL KESEHATAN, 2025)
Background: The postpartum period is a crucial phase that begins after the delivery of the placenta and lasts for six weeks. During this time, mothers experience various physiological and psychological changes that require adequate monitoring. The World Health Organization (WHO) recommends a minimum of four postpartum visits. However, national and regional data indicate low adherence rates. One influential factor in postpartum care compliance is husband support. Objective: To determine the relationship between husband support and postpartum mothers' adherence to follow-up visits at BPM Fifiyanti, Agam Regency.Methods: This quantitative study used an observational analytic design with a cross-sectional approach. The population consisted of postpartum mothers who gave birth at BPM Fifiyanti from January to March 2025, with a total sample of 45 respondents. Data were collected using a validated questionnaire and medical records. Univariate analysis was used to describe respondent characteristics, while the Chi-Square test was used for bivariate analysis at a significance level of p < 0.05. Results: The results showed that 66.7% of postpartum mothers received high support from their husbands, and 71.1% adhered to follow-up visits. The Chi-Square test revealed a significant relationship between husband support and postpartum visit adherence (p = 0.003). Conclusion: There is a significant relationship between husband support and postpartum mothers’ compliance with recommended follow-up visits. This finding highlights the importance of involving husbands in maternal health education and services during the postpartum period.